Optimalization of the Nagari Owned Enterprise Program (BUMNag) Mitra Mandiri in Developing the Potential of Nagari Sungai Pua Agam Regency - Nadya; Rizki Syafril (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2023)
Badan Usaha Milik Nagari Mitra Mandiri Sungai Pua is a business entity established in order to utilize the wealth of Nagari Sungai Pua which has the potential to be developed. Through its program, BUMNag is expected to be maximized in operating it and will be able to benefit the people of Nagari Sungai Pua. This study aims to determine the optimization of the Sungai Pua Nagari "Mitra Mandiri" Owned Enterprise program in developing the potential of Nagari Sungai Pua.. The method in this study uses descriptive qualitative research methods. The research was conducted at the Nagari Owned Business Entity Sungai Pua Agam Regency with the selection of informants using purposive sampling technique. Data validity testing techniques using source and method triangulation techniques. This research was conducted using Siringoringo's optimization theory with indicators of goals, alternative decisions and limited resources. The results showed that the optimization of the Nagari Mitra Mandiri Sungai Pua Owned Business entity program was not optimal. This can be seen from Siringoringo's optimization indicators that alternative decisions have not run optimally and several indicators on limited resources are still an obstacle in the implementation of BUMNag programs. This article also describes the causes, ways that can be done, and future plans that can be done as an alternative in optimizing the program of the Nagari Owned Entity "Mitra Mandiri" Sungai Pua, Agam Regency.